DEVELOPING “ANTI-CYBERBULLYING INTELLIGENCE” INSIDE SOCIAL MEDIA USING JOHARI WINDOW-KEN WATANABE-PROBLEM SOLVING 101 METHODS - Gamayanto, Indra; wibowo, Sasono; Setiadi, De Rosal Ignatius Moses (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2020)
Abstract: Cyberbullying is a complex problem because it produces a large impact on the individuals who experience it. Furthermore, cyberbullying is a problem that may not have found the right solution in this day and sometimes, there is no problem-solving. Furthermore, this research is a development from three research: The Development and Implementation of Wise Netizens (E-Comments) in Indonesia and journals; the journal Developing "Culture Intelligence (CI3) Framework" Inside Social Media Using Johari Window Methods and the journal Developing "Leadership Intelligence (CI2) Framework" Inside Social Media to Develop an Ethical Leader using the Johari Window Method. Moreover, the method used in this research is the Johari window and Ken Watanabe-Problem Solving. The results of this research are the formula CB = P.B2 and the cyberbullying methodology framework 2020-2025 that is useful for overcoming cyberbullying problems in several categories. Key Words: Cyberbullying, Social media, Traditional bullying, Ken Watanabe, Johari Windows